PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE (IOC) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 15 PEKANBARU - Ria Puji Astuti; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This background of research is students’ low result learning of IPS subject at fifth grade SDN 15 Pekanbaru the minimum criteria learning mastery is 75. All of students is 36 students. However, only 14 students’ (38,89%) passed this KKM. Another hand, 22 students (61,11%) could not achievement this KKM with class learning means wae 58.88. This study aim to increase the fifth students’ learning outcome in SDN 15 Pekanbaru on the social science apply Inside Outside Circle (IOC) type of cooperative learning model. This research served data result learning by taken from students’ daily exam before give treatment was 58,88. After give the treatment, get improve be 72.36 on first cycle. After that get improve again be 81,53 on second cycle. Teacher’s activities on first cycle got 58,33 % it’s minus category. Next, second meeting van improve be 70.80% is enough category. Then on second cycle tacher’s activities improved 83.33% that was good category. Next, on second meeting improved be 95.83 % its’ better category. On another side, students’ activities on cycle 1 especially first meeting got 58.33% it was medan minus category. On second meeting improved be 62.50% its enough category. Then on second cycle students’ actvities 79,17% that was good category. Next, on second meeting improve be 91.67% its’ better category. Based on the result of the research, it can proofed that appliement of cooperation type Inside Outside Circle (IOC) learning model to improve students’ social subject learning result at fifth grade SD Negeri 15 Pekanbaru.Keywords: Inside Outside Circle (IOC), IPS learning result